Role of chronic cannabis use: Cyclic vomiting syndrome vs cannabinoid hyperemesis syndrome. (26th June 2019) - Venkatesan, Thangam; Levinthal, David J.; Li, B U. K.; Tarbell, Sally E.; Adams, Kathleen A.; Issenman, Robert M.; Sarosiek, Irene; Jaradeh, Safwan S.; Sharaf, Ravi N.; Sultan, Shahnaz; Stave, Christopher D.; Monte, Andrew A.; et al.
Abstract: Cannabis is commonly used in cyclic vomiting syndrome (CVS) due to its antiemetic and anxiolytic properties. Paradoxically, chronic cannabis use in the context of cyclic vomiting has led to the recognition of a putative new disorder called cannabinoid hyperemesis syndrome (CHS). Since its first description in 2004, numerous case series and case reports have emerged describing this phenomenon. Although not pathognomonic, a patient behavior called "compulsive hot water bathing" has been associated with CHS. There is considerable controversy about how CHS is defined. Most of the data remain heterogenous with limited follow‐up, making it difficult to ascertain whether chronic cannabis use is causal, merely a clinical association with CVS, or unmasks or triggers symptoms in patients inherently predisposed to develop CVS. This article will discuss the role of cannabis in the regulation of nausea and vomiting, specifically focusing on both CVS and CHS, in order to address controversies in this context. To this objective, we have collated and analyzed published case series and case reports on CHS in order to determine the number of reported cases that meet current Rome IV criteria for CHS. We have also identified limitations in the existing diagnostic framework and propose revised criteria to diagnose CHS. Future research in this area should improve our understanding of the role of cannabis use in cyclic vomiting and help us better understand and manage this disorder.